The Maternal–Fetal Interface in Small-for-Gestational-Age Pregnancies Is Associated With a Reduced Quantity of Human Decidual NK Cells With Weaker Functional Ability - Lin, Fang; Yang, Chuan; Feng, Ting; Yang, Shuo; Zhou, Rong; Li, Hong (Frontiers in Cell and Developmental Biology, 2020)
Small for gestational age (SGA) refers to a birth weight that is less than the 10th percentile of the mean weight of infants at the same gestational age. This condition is associated with a variety of complications, and a high risk of cardiovascular and cerebrovascular diseases in adulthood. Decidual natural killer (dNK) cells at the maternal–fetal interface have received significant research attention in terms of normal pregnancy or abortion; however, data relating to SGA are limited. In this study, we aimed to investigate the characteristics and regulatory role of dNK cells at the maternal–fetal interface in SGA. Using immunofluorescence assays, we found that dNK cells maintained close contact with extra-villous trophoblasts, and the number of dNK cells in SGA decreased than in appropriate for gestational age (AGA). Flow cytometry also showed that there was a significantly lower number of dNK cells in SGA (25.01±2.43%) than in AGA (34.25±2.30%)(p=0.0103). The expression of the inhibitory receptor NKG2A on dNK cells and the secretion levels of both perforin and TGF-β1 from dNK cells were significantly higher in SGA than in AGA, while the cytotoxicity of dNK cells in SGA against K562 cells was attenuated. . And compared to AGA, the functional ability of dNK cells in SGA showed significant functional impairment to promote proliferation, migration, invasion, and tube formation, in trophoblast cells or vascular endothelial cells. The abnormal function of dNK cells may affect fetal growth and development, and coule be therefore participate in the pathogenesis of SGA.